Conceptual Models of Social Determinants of Health: A Narrative Review - Sayyed Morteza HOSSEINI SHOKOUH; Mohammad ARAB; Sara EMAMGHOLIPOUR; Arash RASHIDIAN; Ali MONTAZERI; Rouhollah ZABOLI (Tehran University of Medical Sciences, 2017)
Background: There are several conflicting conceptual models to explain social determinants of health (SDH) as responsible for most health inequalities. This study aimed to present these models in historical perspective and provide main component of SDH models as an SES indicators. Methods: This was a narrative study using international databases to retrieve literature dealing with conceptual models of SDH. All publication in English language until Mar 2015 was included. The CASP and PRISMA were used to summarize the literature. Results: Overall, 248 publications were retrieved and screened. After exclusion of irrelevant and duplicates, 94 citations were found to be relevant and 21 publications included in this review. In general, 21 models of SDH were found: some models presented before year 1995(n=4), some models presented between 1995 and 2005 (n=13) and some models presented after 2005 (n=4). However, we found three categories of indicators that contribute to SDH models and that were classic factors, fixed and demographic factors and proxy factors. Conclusion: Reduction of socioeconomic inequalities in health requires understanding of mechanisms and causal pathways; therefore, every country needs to design the specific model. As the available models are for developed countries, lack of a specific model for developing ones is tangible. As there is no gold standard related to SES indicators, therefore, it is proposed to use the various indicators based on life course approach, which leads to understanding and adopting effective policy interventions.